2012
DOI: 10.1016/j.juro.2011.11.105
|View full text |Cite
|
Sign up to set email alerts
|

Status of Oxidative Stress in Patients With Renal Cell Carcinoma

Abstract: Patients with renal cell carcinoma have increased oxidative stress, which is effectively alleviated by curative resection. In patients with benign tumors antioxidant defense mechanisms maintain normal redox status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…Solid tumors endure a severely hypoxic environment, and adaptation to such a hypoxic environment is a critical step in tumor progression. Increases in markers of oxidative stress, such as ROS and nitric oxide, were found in some patients with RCC [39]. In addition, patients with increased parameters of oxidative stress and decreased antioxidant levels were associated with higher grade, stage and metastatic disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumors endure a severely hypoxic environment, and adaptation to such a hypoxic environment is a critical step in tumor progression. Increases in markers of oxidative stress, such as ROS and nitric oxide, were found in some patients with RCC [39]. In addition, patients with increased parameters of oxidative stress and decreased antioxidant levels were associated with higher grade, stage and metastatic disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ROS and NO did not increase in patients with benign tumors when compared to patients with malignant tumors. In patients with metastatic disease who had their tumor surgically removed, ROS production did not decrease and it was associated with the residual disease [6].…”
Section: Introductionmentioning
confidence: 90%
“…In previous study, a decreased activity of total SOD was also observed [9]. Opposite to these results, Ganesamoni et al [10] found the increased activity of SOD in tumour tissue compared to normal kidney tissue.…”
Section: Discussionmentioning
confidence: 81%